Adaptasi Indonesia Caring Dimensions Inventory (CDI): Sifat Psikometrik dan Struktur Faktor - Andria Pragholapati; Eni Hidayati; Anggorowati Anggorowati (Yayasan Healing and Healthcare Education, 2023)
The purpose of this study was to test the construct validity and construct reliability on the Caring Dimensions Inventory (CDI) and examine the components and indicators that can construct the caring variable. The sample in this study was 127 Nursing Students. The research data were analyzed through the SPSS program. Based on the results of data analysis, the components and indicators that build the caring variable are declared valid and reliable. These results indicate that all components and indicators are able to reflect and construct caring variables.